From the Substantialist Subject to the Ethical Self: Examining the Problem Concerning Susan Barton's Substance in Coetzee's Foe through the Lens of Confucianist Reciprocity - Shi, Juhong; Zhu, Gang (Research in African literatures, 2025)
This paper approaches J. M. Coetzee's poetics of reciprocity in the comparative context of Western philosophy and Confucianist reciprocity by analyzing the problems encountered by Susan Barton, the protagonist of his novel Foe , as she navigates the quest for her substantial being. It contends that Coetzee intricately problematizes Susan's substance—an important philosophical concept that equals "being" or "ultimate self"—to delve into his reflections on interpersonal relations. Critiquing the Substantialist conception of subjectivity, which stresses individual determinacy and distinctness, Coetzee envisions a new self–other dynamic that echoes Confucianist reciprocity, which puts an asymmetrically higher demand on the self and maintains that becoming a human being means striving to fulfill one's interpersonal relations rather than being absolutely substantial. Approaching Coetzee's poetics of reciprocity in light of Confucianism offers us an opening through which an ethical self–other relation might be reconstructed to reverse the tension between the self and the other in Western philosophy.